SINGLE BLIND PLACEBO-CONTROLLED STUDY ON COMPARISION OF EFFECTS OF ZINGIBER OFFICINALE BEFORE AND AFTER TREATMENT IN HYPERLIPIDEMIA - Qudoos, Abdul; Nia, Khazlid; Hakro, Shahina; Murad, Shah (Journal of Drug Delivery and Therapeutics, 2016)
Hyperlipidemia had have proved in many research studies causing atherosclerosis, coronary artery disease, angina and myocardial infarction. Hypolipidemic drug’s low compliance made medicinal herbs to replace conventional hypolipidemic agents for treating primary or secondary hyperlipidemic patients. Zingiber Officinale (Ginger) is one of those medicinal herbs.  This research was conducted at General Hospital Lahore Pakistan from March to May 2015. It was single-blind placebo controlled study. Inclusion criteria was primary and secondary hyperlipidemic patients age range from 18 to 65 years. Male and female patients were included in this work. Randomly selected eighty patients were divided in two equal numbers. Group-I was tested group and Group-II was on placebo therapy. Their base line values of LDL-cholesterol and plasma total cholesterol were measured in Biochemistry laboratory of the Hospital.  When used in 40 hyperlipidemic patients this herb’s paste preparation reduced LDL-cholesterol and plasma total cholesterol significantly. Mean values of LDL-cholesterol and plasma total cholesterol with SEM before and after treatment were calculated and analyzed biostatistically by using SPSS version 5.0. P-values >0.05 were used for non-significant change in parameters. P-values